Good Offices Initiative of Turkey's Diplomacy Policy in The Russia-Ukraine Conflict Resolution Approach in 2022 - Cahyani, Desak Nyoman Gita; Dwi Atmaja, Bima Kumara (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 3 (2023)DO - 10.24843/JMHU.2023.v12.i03.p04, 2023)
This writing aims to answer questions related to Turkey's attitude toward initiating itself in good offices effort during the Russia-Ukraine conflict that has been going on since February 2022. This is an interesting subject because Turkey dares to take an independent diplomatic policy in responding to the Russia-Ukraine conflict. This paper uses normative legal research methods and applies data collection techniques in the form of literature studies using primary and secondary legal materials, also data processing and analysis using descriptive qualitative analysis techniques. This study concludes that the basis for consideration of Turkey's foreign policy is that it is in a neutral position and offers good offices, namely based on the principles of its foreign policy, the powerlessness of the United Nations, and to protect Turkey's national interests. Then, the capability of Turkey to hold negotiations can be viewed from Turkey's neutral status. Lastly, Turkey has made significant contributions to the successful holding of mediation in Antalya and Istanbul, also an achievement of the Black Sea Grain Initiative.